BUTTERFLY HOUSE AS A GENETIC LEARNING MEDIA - Halimah, Mimi (Jurnal Pengajaran MIPA, 2019)
Implementation of a good learning process should use appropriate learning media and can support contextual learning, and one such medium is a butterfly house. The research method is quasi-experiment. The result of the research shows that there is an increase of student learning result of biology teacher candidate using butterfly house as a medium of learning in Genetics course significantly in the medium category. This increase is not in the high category because there are many technical obstacles in the process of preserving butterflies, but these are the technical constraints that make the process of solving the problem in maintaining butterflies can be honed. Thus the use of butterfly house as a learning medium of Biology is to bridge the difficulty of studying butterflies in the wild and lack of study of butterflies using the media animation.